Effects of prenatal exposure to methylmercury in children auditory processing - Marilene Danieli Simões Dutra; Marcia Cavadas; Iracina Maura de Jesus; Elisabeth Oliveira Santos; Volney de Magalhães Câmara (Instituto de Estudos em Saúde Coletiva da Universidade Federal do Rio de Janeiro, 2016)
Abstract Objective: to assess the central auditory processing of children exposed to mercury during the prenatal period. Design/Study sample: this study evaluated 90 children age eight to ten years, of both genders divided into two groups according to the levels of mercury exposure during the prenatal period: the study group (SG) was composed of children who had total mercury levels in umbilical cord blood samples equal or higher than 8µg/L, and the control group (CG) of children who had Mercury levels lower than 8µg/L. The procedures included a questionnaire, tonal threshold audiometry, word recognition audiometry, tests that assess auditory processing skills; and analysis of the total levels of mercury in umbilical cord blood samples collected at birth. Result: The SG presented mean total mercury in umbilical cord blood of 19.36µg/L and the CG had mean of 4.78µg/L. Regarding the tests that assess central auditory processing, the SG showed worse performance than the CG, and there was a statistically significant difference observed in the Staggered Spondaic Word Test. Conclusion: Children presented disorders in the tests that assess central auditory processing, indicating a possible effect of prenatal exposure to mercury in the central auditory system.